The Role of Library for the Semester System: A Case of Prithvi Narayan Campus - Baral, Uma Nath (Prithvi Academic Journal, 2019)
As part of reform of its higher education, Tribhuvan University (TU) has recently introduced the semester system for assuring quality education in its master’s programs. As a constituent campus of TU, Prithvi Narayan Campus has started the semester system from the academic session 2018 for its master levels' programs. To successfully instigate the semester system, the institution has to meet certain requirements such as it should have full-time and energetic students, dedicated and innovative teachers, good administration, proper curricula, a resourceful library, a learning environment, and a prompt academic calendar. Among these requirements, the library is vital to enhance the knowledge of the students and significantly maintains quality in education. The role of the library is necessarily dependent upon the educational objectives of the higher institution. Therefore, the main objective of this study is to find out students’ perceptions towards the role of the library for the effective functioning of the semester system. A questionnaire survey method was adopted to collect data for the study. In addition, informal conversations with some students, faculties, and the librarian were also conducted in order to get required information to meet the objective of the study.